69.4k views
0 votes
all you need is in the photo please answer fast please helpppppp do not do step by step pleaseeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeee

all you need is in the photo please answer fast please helpppppp do not do step by-example-1

1 Answer

4 votes

The average rate of change of function y between [a, b] is computed as follows:


(y(b)-y(a))/(b-a)

In this case, a = 1, b = 2, and:

y = x² + 3x - 2

y(1) = 1² + 3(1) - 2

y(1) = 1 + 3 - 2

y(1) = 2

y(2) = 2² + 3(2) - 2

y(2) = 4 + 6 - 2

y(2) = 8

Then, the average rate of change is:


(8-2)/(2-1)=6

User Allis
by
5.2k points